Peranan Nilai dan Jangka Waktu Jatuh Tempo Kupon Diskon terhadap Respon Pembelian Konsumen (Studi pada Barang Convenience) - M. Riza Firdaus (Jurnal Aplikasi Manajemen, 2010)
This study focuses especially on the Behavioral Influence Perspective of the non-psychological approach that is still rarely performed. The purpose of this study is to test and to prove empirically whether there are differences in responses based on the difference between the coupons value and the expiration period of coupons. This is conducted in order to determine the conditions when the coupons are effective as a means of sales promotion. The samples of this research are 300 participants and 25 participants for the control group. The research results indicate that instant coupon for all coupon values, and non instant coupon with 25% of the product total value, with a maximum period of 7 days before the expiry date, will have a positive impact when they are given to new customers.Keywords: Coupon Value, expiration period of coupons, Interaction between coupon value and expiration period of coupon, Instant Coupons, non instant coupons